Application of decision trees for wage forecasting - Hancco Vargas, Corina (2023)
This article details the process that was carried out for the salary forecast in a database of a census given in 1996, where the Python programming language was used, for the analysis of the data of the dataset the Google Colab server was used to execute the algorithms in the cloud, since the team considered that the speed of data analysis in Google Colab is faster. One of the data mining techniques was also used to classify the variables using decision trees that have the ability to graphically represent several alternative solutions in order to determine the most effective courses/routes of action for the classification of the obtainment. of a person's salary.